Influence of Insurance Status and Demographic Factors on Outcomes Following Tracheostomy. (7th August 2020) - Bahethi, Rohini; Park, Christopher; Yang, Anthony; Gray, Mingyang; Wong, Kevin; Iloreta, Alfred; Courey, Mark
Abstract : Objectives/Hypothesis: Little data exists regarding the relationship between socioeconomic and demographic factors and tracheostomy outcomes. The goal of this study was to determine associations between socioeconomic status (SES), demographic factors, and insurance status with hospital length of stay (LOS), intensive care unit (ICU) LOS, and mortality following tracheostomy. Study Design: Retrospective cohort study. Methods: A retrospective analysis of all patients who underwent tracheostomy at an urban tertiary‐care academic hospital from 2016 to 2017 was performed. Patients were aggregated into low‐, middle‐, and high‐income brackets. Other variables included age, sex, race, ethnicity, body mass index, and Charlson Comorbidity Index (CCI). Outcomes included hospital and ICU LOS, in‐hospital mortality, and 30‐day mortality following tracheostomy. Outcomes were compared using Kruskal‐Wallis tests for continuous variables and χ 2 or Fisher exact tests for categorical variables. The α level was set to .05. Results: In total, 523 patients were included in the study. Patients from high‐income areas were more likely to be male ( P  < .01), white ( P  < .01), and had lower body mass index ( P  = .04). On multiple regression analysis, Hispanic or Latino ethnicity was associated with an increased odds of 30‐day mortality (odds ratio [OR]: 4.43, P  = .020). CCI was also associated with increased odds of 30‐day mortality (OR: 1.12, P  = .039). Conclusions: Lower SES was not associated with increased morbidity or mortality after tracheostomy. Although Hispanic patients tended to have a lower CCI score, they had increased 30‐day mortality, suggesting there are factors specific to this population that may influence outcomes, and future targeted studies are warranted to study these relationships. Level of Evidence: 4 Laryngoscope, 131:1463–1467, 2021